(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article examines the artistic and philosophical foundations of the fable genre in the age of Classicism, with particular emphasis on the principles of order, reason, and morality. During the seventeenth and eighteenth centuries, Classicism established a rational and normative aesthetic system grounded in the ideals of harmony, clarity, and discipline derived from antiquity and Enlightenment philosophy. Within this framework, the fable emerged as one of the most effective literary genres for moral instruction and philosophical reflection. Applying the IMRAD structure, the study analyzes how Classical aesthetics shaped the structure, imagery, and didactic function of the fable genre. The article demonstrates that the Classical fable functioned not merely as a literary form, but as a philosophical instrument aimed at rationalizing human behavior, promoting ethical norms, and reinforcing social order.